Evaluación de la producción de Vodka artesanal "La Destilería" haciendo uso de Passiflora edulis (Maracuyá) como fruta adicional (2021)
In this research project, the addition of passion fruit (Passiflora edulis) was evaluated as a raw material to be incorporated in the production process of artisanal vodka "La Destilería" in order to give the liquor added value without neglecting the characteristics vodka base. For this, a previous heat treatment is established for the fruit, seeking not to negatively affect its organoleptic properties; Different experiments are carried out (2) to establish which is the best stage for the addition of the fruit (maceration or fermentation), resulting in fermentation, thanks to a sensory test and survey carried out among ordinary people.